Socially responsible investments (SRIs) in the European Arctic:new pathways for global investors to outperform conventional capital investments? - Braun, Adrian (Routledge, 2020)
Socially responsible investments (SRIs) are on the rise in an effort by the global finance sector to diversify the portfolio of green financial products. The kickoff for this development goes back to the years around 2005, when large-scale financial institutions put the concept of environmental, social and governance (ESG) on the agenda as a response to rising pressure on institutional and other large-scale investors’ investment strategies. Climate bonds are effective investment products that allow issuers to get access to capital for a certain initiative to adapt to or mitigate the negative effects of a warming climate. Particularly in the Arctic latitudes, SRIs can play a pivotal role to counteract negative ecological impacts and to enable improved living conditions and social sustainability in the local societies. Investors have the opportunity to gain awareness and experience of these issues and to build up large-scale benefits from them. This study provides insights into current developments and the overall relevance of SRIs in the European Arctic and the global economy. Learning about applicable tools and mechanisms of green investments, climate-related financing and efforts to minimize industrial ecological footprints enables investors to ground their understanding of modern demands related to the environment and society.